Digital Transformation of Bank Syariah Indonesia Services and Its Impact on Financial Inclusion - Abdulloh, Muhamad (Invest Journal of Sharia & Economic Law, 2023)
Islamic financial inclusion is the openness of providing access and use of a variety of convenient and affordable financial services by sharia. In supporting the realization of the Sharia financial inclusion target and the Indonesian Sharia Banking Development Roadmap (RPSI) for 2020-2025, Bank Syariah Indonesia strives for customer convenience and comfort by providing access to various products and services digitally. The research method uses a type of qualitative descriptive research with a library research method. The types of data used are primary data and secondary, primary data obtained from BSI's official website and result reports, secondary data obtained from other people's research, documentation data, and studies relevant to this study. The purpose of the study was to determine 1) the level of financial literacy index and Islamic financial inclusion index in Indonesia. 2) to recognize Bank Syariah Indonesia's efforts in seeking Sharia financial inclusion targets and the Indonesian Sharia Banking Development Roadmap (RPSI) for 2020-2025. The results showed that the level of Islamic financial literacy and inclusion index in 2022 increased to 9.14% and 12.12% from the previous 8.93% and 9.10%